The Use of Video for Distance Learning During Covid-19 Pandemic: Students’ Voice - Alvi Raihan Utami; Lulud Oktaviani; Ive Emaliana (Universitas PGRI Adi Buana Surabaya, 2021)
During covid-19 pandemic, teachers need to change the activity from a face-to-face into distance learning activity. There may many methods and media used by the teacher, one of them is video. One of the aims is to assist teachers in explaining the material and attracting students' interest. Hence, this study aims to find out the benefits of the use video in teaching and learning activity in pandemic situation. In this study, the researchers investigated what the benefit of the use of video for English learning as perceived by students in Covid-19 pandemic situation. the researchers used qualitative method in this research. The instruments used in this study are questionnaire and interview. The researchers took the data from two classes, which were XI KI I and XI KI III of SMK SMTI Bandarlampung.The research findings shows that students had positive experience when using video as medium in teaching and learning English as a foreign language. Moreover, most of the students agreed that video gives the advantages to the students, such as the increasing of motivation in learning, acquiring new vocabularies, and improving the pronunciation of Englsih words. During covid-19 pandemic, teachers need to change the activity from a face-to-face into distance learning activity. There may many methods and media used by the teacher, one of them is video. One of the aims is to assist teachers in explaining the material and attracting students' interest. Hence, this study aims to find out the benefits of the use video in teaching and learning activity in pandemic situation. In this study, the researchers investigated what the benefit of the use of video for English learning as perceived by students in Covid-19 pandemic situation. the researchers used qualitative method in this research. The instruments used in this study are questionnaire and interview. The researchers took the data from two classes, which were XI KI I and XI KI III of SMK SMTI Bandarlampung.The research findings shows that students had positive experience when using video as medium in teaching and learning English as a foreign language. Moreover, most of the students agreed that video gives the advantages to the students, such as the increasing of motivation in learning, acquiring new vocabularies, and improving the pronunciation of English words.